2021
DOI: 10.3390/electronics10182290
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Inverted CdSe/ZnS-Based Light-Emitting Diodes by Nonvacuum Technique ZTO as the Electron-Transport Layer

Abstract: CdSe/ZnS quantum dots (QDs) have attracted great consideration from investigators owing to their excellent photo-physical characteristics and application in quantum dot light-emitting diodes (QD-LEDs). The CdSe/ZnS-based inverted QD-LEDs structure uses high-quality semiconductors electron transport layers (ETLs), a multilayered hole transporting layers (HTLs). In QD-LED, designing a device structure with a minimum energy barrier between adjacent layers is very important to achieve high efficiency. A high mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Although the hole mobility in organic HTL is much lower than the electron movement in ETL, the unbalanced carrier insertion within the QD-LEDs is mainly caused by the inadequate hole injection of the organic HTL. To establish carrier-injection balance in the QD-LEDs, It is still considered efficient to design a distinct HTL that has excellent hole mobility as well as deep HOMO [15]- [17]. Additionally, recent studies have shown that the performance of QD-LEDs can degrade faster due to electron leakage from organic HTL.…”
Section: Introductionmentioning
confidence: 99%
“…Although the hole mobility in organic HTL is much lower than the electron movement in ETL, the unbalanced carrier insertion within the QD-LEDs is mainly caused by the inadequate hole injection of the organic HTL. To establish carrier-injection balance in the QD-LEDs, It is still considered efficient to design a distinct HTL that has excellent hole mobility as well as deep HOMO [15]- [17]. Additionally, recent studies have shown that the performance of QD-LEDs can degrade faster due to electron leakage from organic HTL.…”
Section: Introductionmentioning
confidence: 99%